(untitled) (Canadian Journal of Native Studies, 2026)
Ontario Tech University is both small in student size and young in relation to the Canadian academic landscape. With its emphasis on technology well established, the university is shifting some of its attention to address the need to include Indigenous knowledge and history through course offerings. This paper illustrates contextual details of the university, the process of the first Indigenous Studies course creation, and our work in listening to the stories of the students. We explore the demographics and history of Ontario Tech University and Durham Region, where it is situated. We describe the formation of the community group that created the course, and review our methodology addressing Indigenist research and Indigenous pedagogical approaches. We include some of the conversations we had during the writing of this paper, demonstrating layers of story and relationality. Finally, we conclude with a discussion of the stories shared by the students, noting some of the signs for hope and for caution.